Clinical researchOsteopenia and osteoporosis in patients with dermatitis herpetiformis. Effect of gluten-free diet - Żebrowska, Agnieszka; Waszczykowska, Elżbieta (Archives of Medical Science, 2007)
Introduction: Dermatitis herpetiformis (DH) is a rare blistering disease which is accompanied by gluten-sensitive enteropathy. Intolerance of gluten is the most important feature of both diseases. In 70% of the cases, lesions in the small intestines of DH patients are histologically identical with those observed with celiac disease. However, those observed with celiac disease can be less intensive. Even though intestinal villous atrophy is observed in a majority of patients, clinical symptoms of malabsorption, especially diarrhea, are evident in only a portion of the cases. Demonstration of significantly lower bone mineralization in some patients using dual-energy X-ray absorptiometry (DXA) suggested the possibility of malabsorption complication in the form of osteoporosis in DH patients. The aim of the study was to evaluate the incidence of skeletal mineralization disturbances in patients with DH and to determine whether adherence to gluten-free diet can prevent these patients from the development of osteoporosis. Material and methods: DXA examination of the lumbar spine and concentration of bone rebuilding markers in blood serum were carried out in 37 patients diagnosed with DH and in 27 healthy controls. Results: Osteopenia and osteoporosis was found in more than half of the examined patients with DH. Postmenopausal women with a long history of the disease are at a higher risk. There is, however, increased rate of accelerated loss of bone mass in men and premenopausal women under the age of 65. Conclusions: The obtained results allowed us to draw the following conclusion: DH is a pathological condition which is burdened with complication in the form of osteoporosis.